Kajian Etnobotani Tanaman Bambu dan Pemanfaatannya di Kampung Gombong Nyiru Kabupaten Bandung Barat sebagai Implementasi Etnopedagogi Materi Biologi pada Kurikulum Merdeka : (Ethnobotanical Study of Bamboo Plants and Their Utilization in Gombong Nyiru Village, West Bandung Regency as an Ethnopedagogy Implementation of Biology Materials in the Independent Curriculum) - Nurani Rahmawati, Dini; Sriyati, Siti (BIODIK, 2024)
Various types of plants thrive in Indonesia, one of which is bamboo. The potential abundance of bamboo and its local wisdom values are considered necessary to be integrated with biology learning activities in accordance with the character of the independent curriculum. However, there is still a gap between the demands of the independent curriculum which must integrate local wisdom into learning and the lack of research related to Indonesia's culture with science studies and its analysis of the independent curriculum. This study aims to examine the ethnobotany of bamboo plants and their utilization in Kampung Gombong and is associated with ethnoscience in the implementation of ethnopedagogy for learning Biology material in the Independent Curriculum. The method used in this research is a qualitative method. Determination of the sample area was carried out by purposive sampling. Determination of informants was carried out using the Snowball Sampling technique. The number of informants in this study was 3 people, consisting of 1 community leader and 2 bamboo craftsmen. Data and information collection techniques were carried out by preliminary surveys, observations, interviews, documentation and literature studies.  Data analysis was carried out descriptively qualitatively as outlined in the form of narratives, tables and figures. The results of the research obtained there are 2 types of bamboo, namely bamboo tali (G. apus) and bamboo gombong (G. pseudoarundinacea) in the village of Gombong Nyiru utilized for handicrafts of household appliances and as building construction. Tali bamboo has a long, flexible and malleable stem structure making it suitable for making woven household appliances, while gombong bamboo has a strong, sturdy and large diameter stem structure making it suitable for making building construction. The results of this ethnoscience study of bamboo plant utilization can support biology learning activities in E phase high school material on biodiversity, classification, and environmental change. In addition, the ethnoscience of bamboo plants can also be related to biology material in phase F material on morphological structure and function of plant organs as well as food nutrition and nutrition material. Integration of local wisdom with school learning in the independent curriculum can be included in subjects in intracurricular activities and co-curricular project activities to strengthen the profile of Pancasila students. Suggestions for further research are that more and in-depth studies need to be carried out related to the ethnobotany of local plants in Indonesia which can be integrated in the ethnopedagogy of learning biology material in the independent curriculum. Abstrak. Berbagai jenis tanaman tumbuh subur di Indonesia salah satunya tanaman bambu. Potensi kelimpahan bambu dan nilai-nilai kearifan lokalnya dinilai perlu untuk diintegrasikan dengan kegiatan pembelajaran materi biologi sesuai dengan karakter dari kurikulum merdeka. Namun, masih ada gap antara tuntutan kurikulum merdeka yang harus mengintegrasikan kerifan lokal ke dalam pembelajaran dengan masih minimnya penelitian terkait budaya yang dimiliki Indonesia dengan kajian sains dan analisisnya terhadap kurikulum merdeka. Penelitian ini bertujuan untuk mengkaji etnobotani tanaman bambu dan pemanfaatannya yang ada di Kampung Gombong dan dikaitkan dengan etnosains dalam implementasi etnopedagogi pembelajaran materi Biologi pada Kurikulum Merdeka. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Penentuan daerah sampel dilakukan secara purposive sampling. Penentuan informan dilakukan dengan teknik Snowball Sampling.Teknik pengumpulan data dan informasi dilakukan dengan survei pendahuluan, observasi, wawancara, dokumentasi dan studi literatur. Analisis data dilakukan secara deskriptif kualitatif yang dituangkan dalam bentuk narasi, tabel dan gambar. Hasil penelitian didapat ada 2 jenis bambu yaitu bambu tali (G. apus) dan bambu gombong (G. pseudoarundinacea) di kampung Gombong Nyiru. Bambu tali memiliki struktur batang yang panjang, lentur dan mudah dibentuk sehingga cocok untuk dibuat menjadi kerajinan anyaman alat-alat rumah tangga, sedangkan bambu gombong memiliki struktur batang yang kuat, kokoh dan berdiamter besar sehingga cocok untuk membuat konstruksi bangunan. Hasil kajian etnosains pemanfaatan tanaman bambu ini dapat mendukung kegiatan pembelajaran biologi pada materi SMA fase E materi keanekaragaman hayati, klasifikasi, dan perubahan lingkungan. Selain itu, etnosains tanaman bambu juga dapat dikaitkan dengan materi biologi pada fase F materi struktur morfologi dan fungsi organ tumbuhan serta materi nutrisi dan gizi makanan. Pengintegrasian kearifan lokal dengan pembelajaran di sekolah pada kurikulum merdeka dapat dimasukan ke dalam mata pelajaran pada kegiatan intrakulikuler dan kokulikuler kegiatan projek penguatan profil pelajar Pancasila. Saran untuk penelitian selanjutnya yaitu perlu dilakukan kajian lebih banyak dan mendalam terkait etnobotani tanaman lokal yang ada di Indonesia yang dapat diintegrasikan dalam etnopedagogi pembelajaran materi biologi pada kurikulum merdeka.